Contextual Mathematical Modelling: Problem-Solving Characterization and Feasibility - Zehavit Kohen; Ortal Nitzan-Tamar (Education Sciences, 2022)
The current study investigates contextual mathematical modelling (MM) problems that were retrieved from authentic workplace situations and simplified for formal secondary school math lessons. First, the study aims to characterize contextual MM problems according to Schoenfeld’s framework of problem-solving (PS). Second, it aims to investigate the perceptions of two stakeholder groups: (1) math experts and policymakers and (2) math teachers with respect to the characteristics of the contextual MM problems and their feasibility regarding implementation in secondary school education. Based on the Delphi methodology, we employed two phases for our analysis: an open-ended questionnaire to interview ten stakeholders and, subsequently, a Likert-type questionnaire to collect data from 122 stakeholders. The main results indicate that the contextual MM problems are characterized by PS. A similar view was expressed by different stakeholder groups, and no differences were caused by various background variables, such as educational level or STEM background. Additionally, the findings revealed that both stakeholder groups perceived that it is highly feasible for these problems to be integrated into secondary school education. This study contributes theoretically to the interrelationship between MM and PS frameworks, and provides practical recommendations for the implementation of contextual MM problems in secondary schools by applying PS skills.